Emerging Trends of Aggressive Movie Marketing:Lessons Learned from Ghajini - Mutsuddi, Indranil; Mutsuddi, Rimi (Indian Journal of Marketing, 2009)
Over the last few years film makers in India had felt the strategic need of gearing up their distribution and promotional drives in order to make a mark in the box office charts. Trends in the Indian film industry since the year 2005 had shown that the shelf life of films had gone down drastically. Along with this issue, the film industry like any other business organization had faced the ill effects of economic meltdown and terror threats that have significantly affected business opportunities across the nation. In this context, the success of the recent Bollywood movie Ghajini and way it had been promoted to the heart of the audience can be considered as quite an exceptional turnaround case and a management lesson for several business organizations struggling in the recessive business environment. This paper makes an attempt to analyze Ghajini’s success in the light of its aggressive marketing and promotional strategies.